Rethinking Enterprise Policy Can Failure Trigger New Understanding? - Bridge, S. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2010)
Policies to increase the level of enterprise and entrepreneurship, in many countries and regions, have often failed. This book explores this and gives alternative views to derive a different model, based on social influence, which is consistent with the evidence and which might therefore lead to better policy.